Sumar Creative: um aplicativo de solicitação de serviços gráficos para divulgação de eventos e propagandas - Silva, Jonison Alfaia da (Brasil, 2024)
The present work deals with the creation of a digital application, Sumar Creative, which is an innovative app dedicated to requesting graphic services for event promotion and advertising. In an increasingly digital world, the need for quality graphic materials for event promotion becomes essential. Sumar Creative emerges as a solution to streamline this process, connecting clients with designers efficiently and conveniently. In this context, the aim of this work was to develop an application for requesting graphic services for event promotion and advertising. The methodology consisted of three fundamental stages: literature review, application development, and application evaluation/testing. The gathered results were positively evaluated by those who participated in the research. In summary, the implementation of this project, which focused on the creation of the Sumar Creative app, represents an innovative and efficient response to the growing demand for quality graphic materials in event promotion and advertising.